2021
DOI: 10.1590/1984-0462/2021/39/2020007
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Status, Physical Activity, Sedentary Behavior, Diet, and Lifestyle in Childhood: An Analysis of Respiratory Diseases in Adolescence

Abstract: Objective: To evaluate the association between nutritional status, physical activity, sedentary behavior, diet, and lifestyle in childhood with respiratory diseases during adolescence. Methods: Prospective study conducted in São Caetano do Sul, São Paulo - Brazil, as part of the International Study of Childhood Obesity, Lifestyle and the Environment (ISCOLE). During childhood, indicators of lifestyle (body composition, physical activity, sedentary behavior, diet) and family environment were measured in 2012… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…The vast majority of the literature suggesting an association between physical activity and asthma in children is based on cross-sectional studies that rely primarily on self-reported physical activity (15,36). However, studies that utilized accelerometers to measure physical activity found little to no association between physical activity and asthma in children (32,33,38). These ndings suggest that the relationship between physical activity and asthma may be more complex than initially thought, with a potential U-shaped association where both very low and very high levels of physical activity could contribute to exacerbating asthma symptoms (18).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The vast majority of the literature suggesting an association between physical activity and asthma in children is based on cross-sectional studies that rely primarily on self-reported physical activity (15,36). However, studies that utilized accelerometers to measure physical activity found little to no association between physical activity and asthma in children (32,33,38). These ndings suggest that the relationship between physical activity and asthma may be more complex than initially thought, with a potential U-shaped association where both very low and very high levels of physical activity could contribute to exacerbating asthma symptoms (18).…”
Section: Discussionmentioning
confidence: 99%
“…Several factors in uence physical activity (PA) levels in children, including age, diet, access to resources, access to green spaces, and neighborhood walkability (32,36). Notably, children with asthma are less likely to engage in PA (31).…”
Section: Other Outcomesmentioning
confidence: 99%
See 3 more Smart Citations